The efficacy of ondansetron in comparison with pethidine for prevention of shivering in pregnant patients undergoing a cesarean sectionwith spinal anesthesia - Bambang Suryono, Ferianto Pandit S (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
Postanesthetic shivering (POS) is a common complication following spinal anesthesia. Severaldrugs have been used to prevent POS, including ondansetron and pethidine. This study wasconducted to compare the efficacy of ondansetron 8 mg with pethidine 0.4 mg/kg BW forprevention of shivering in pregnant patients undergoing a cesarean section with spinal anesthesia.This is a double blind controlled trial involving 96 pregnant patients between the age 18-40years with ASA physical status I-II, gestational age of 37-42 weeks, body weight of 40-70kg orBody Mass Index (BMI) <30, body height >145 cm who underwent a cesarean section withspinal anesthesia in Dr. Sardjito General Hospital, Yogyakarta and affiliated hospital. Exclusioncriteria included patients or families who refused to participate in the study, having a history ofallergy to bupivacaine, ondansetron, and pethidin, patients with a fetus known to have congenitalabnormalities earlier, body temperature early > 38 ÂºC or <36 ÂºC, pregnancy with complications(PEB, eclampsia, HELLP syndrome), and pregnant patients with heart disease (severe hypertension,heart trouble, abnormal heart valves). The patients were randomized into two groups i.e. 48patients of group ondansentron receiving intravenous ondansetron 8 mg and 48 patients ofgroup pethidine receiving intravenous pethidine 0.4 mg/kg BW. The patients were observed foroccurence and severity of POS, postoperative nausea and vomiting. The results showed thattwo patients (4.2%) on the ondansetron group and six patients (12.5%) on the pethidine groupexperienced of POS. Moreover, the efficacy of ondansetron in the prevention of POS (95.8%)was higher than pethidine (87.5%). However, there were not significantly different (p>0.05).The incidence of nausea on the ondansetron group (4.2%) was lower than the pethidine group(16.7%) (p<0.05). However, no significant difference in the incidences of vomiting was observedbetween the ondansetron (0%) dan the pethidine (4.2%) groups (p>0.05). In conclusion, theefficacy of ondansetron 8 mg is comparable to pethidine 0.4 mg/kgBW for prevention of shiveringin pregnant patients after spinal anesthesia.